Assessing the impact of Financial Obstacles on Manufacturing Firm's capacity utilization: Bayesian Approach - Hassan, Arab Dahir; Ozcan, Razim (UI Scholars Hub, 2023)
This study aims to investigate the relationship between financial obstacles and the capacity utilization of manufacturing firms. This study departs from previous studies in the literature by employing Bayesian linear regression analysis. The results demonstrate that financial constraints have a considerable negative effect on the capacity utilization of manufacturing enterprises, but access to credit lines has a positive effect. The sample consists of 1,494 private manufacturing firms in 31 Europe & Central Asian countries. Financial obstacles were perceived as the major impediment to business operations by 65% of the enterprises in the survey. Furthermore, 52% of enterprises in the sample have access to loans from financial institutions, while 47% have no access to credit lines. This suggests that the manufacturing sector's ability to access financial market resources and overcome financial obstacles serves as both the sector's lifeblood and a major hurdle.